Novel Nondestructive Technique to Determine Optimum Harvesting Stage of ‘Ataúlfo’ Mango Fruit - Osuna-Garcia, Jorge A.; Olivares-Figueroa, Jesús Daniel; Toivonen, Peter M.A.; Pérez-Barraza, Ma. Hilda; Goenaga, Ricardo; Graciano-Cristóbal, María J. (JOURNAL OF ADVANCES IN AGRICULTURE, 2021)
A portable spectrometer was validated to determine optimum harvesting stage of ‘Ataúlfo’ using dry matter and skin color as fruit indicators. To build the model, samples were collected as follows: a. Unripe; b. Green Mature 1; c. Green Mature 2; d. Green Mature 3; and e. Fully mature. Fruit were scanned with a near infrared spectrometer at three temperatures (15, 25, and 35 °C). Skin color (‘a’ value) was measured with a Minolta 400 colorimeter. DM was attained in a conventional oven by drying samples for 72 h at 60 °C. Model was built and validated three times. The best model linearity was obtained on skin color ‘a’ (R2 = 0.98), whereas for DM the R2 was only 0.70. For the first validation, the best predicted value was skin color ‘a’ with an R2 = 0.9144, followed by DM with an R2 = 0.7056. On the second validation, the adjusted predicted value for skin color ‘a’ had an R2 = 0.8798, while DM had an R2 = 0.4445. When comparing NIR versus Heat Units Accumulation, in Nayarit, ‘Ataúlfo’ skin color average difference between the spectrometer vs the colorimeter was only -0.04. For ‘Ataúlfo’ from Sinaloa, skin color average difference was only -0.06, but the correlation was higher (R2 = 0.90). In conclusion, measuring skin color with the NIR spectrometer has potential as a nondestructive technique to determine the optimum harvesting stage of ‘Ataúlfo’ mango.